Intraosseous mucoepidermoid carcinoma of the mandible – a rare case report - Shailaja Sankireddy; Atul Kaushik; Vinod Vijaychander; Asha Latha gannepalli; Bhargavi Krishna Ayinampudi; Sridevi Koduri (Revista Sul-Brasileira de Odontologia, 2015)
Mucoepidermoid carcinoma (MEC) is the most common salivary gland malignancy. The majority of these tumors arises in the parotid and minor salivary glands but may rarely develop intraosseously. Primary intraosseous mucoepidermoid carcinoma (PIOC) of the jaw bones is an extremely rare malignant salivary gland tumor. Very few cases have been reported in the literature to date. Case report: The current manuscript highlights clinical and radiographic features of a rare case of PIOC in a 32 year old Indian female patient. Conclusion: All the dental practitioners should be aware of the protean features of central MEC. These lesions should be included in the differential diagnosis of unilocular and multilocular radiolucent lesions of the jaws. An early and accurate diagnosis is important so that the neoplastic transformation must be identified and treated effectively.